The timing of evaluation of genebank accessions and the effects of biotechnology - Koo, Bonwoo; Wright, Brian D. (International Food Policy Research Institute, 1999)
The lack of ex-ante evaluation of germplasm in genebanks has been the single most prevalent and long-standing complaint of plant breeders about the management of genebanks. Advances in biotechnology offer the possibility of faster, cheaper, and more efficient evaluation methodologies. Will these new technologies favor ex-post evaluation, as some expect, or will it lead to more ex-ante evaluation? Will it also lead to earlier development of varieties with disease resistance traits in anticipation of actual infestations? Will the prospect of further advances in biotechnology favor delay of evaluation and development? This paper addresses these questions in the case of evaluation of germplasm for resistance to a disease.